A Carcinoid Tumor in the Urinary Bladder With Uncommon Clinicopathological Presentation - Krishnendu Mondal; Rupali Mandal (Iranian Society of Pathology, 2017)
Background: Carcinoid tumors usually originate from the enterochromaffin cells located in gastrointestinal tract and bronchopulmonary system. They may rarely arise in the urinary bladder, where this can be eventually miscued as any other commoner bladder neoplasms. The current study was conducted to connote an uncommon clinicopathological presentation by a carcinoid tumor in the urinary bladder. Case: A 52-year-old male, who initially experienced obstructive urinary symptoms, underwent cystourethroscopy  to remove a tumor in the urinary bladder. The tumor exhibited insular, trabecular, and organoid architecture on histology without any necrosis or mitosis, stained positively with chromogranin A, and thereby, confirmed the diagnosis of a pure carcinoid tumor. Conclusion: Carcinoid tumors rarely arise in the urinary bladder and other genitourinary organs. But, several other and relatively more common bladder neoplasms may often deceptively simulate it. This dilemma could be resolved easily with the application of proper immunohistochemistry (IHC) in neuroendocrine tumors.